Effectiveness of Eco Enzyme for Inducing Flower Growth in Dendrobium Sonia-ersakul Orchids - Azuhro, Vionika; Dzakiy, M. Anas; Minarti, Ipah Budi (Jurnal Pijar Mipa, 2024)
Orchid plants are ornamental plants with various shapes, colors, and sizes, exhibiting unique characteristics that make them a special attraction for enthusiasts of ornamental plants. Among them is the Dendrobium orchid, which belongs to the genus of orchids known for its diverse types and beauty. Enhancing the growth and quality of Dendrobium Sonia-ersakul orchid flowers can be achieved through proper fertilization. The fertilizer in this research is derived from liquid organic fertilizer, Eco Enzyme. This research aims to assess the impact of Eco Enzyme on the induction of flowering growth in Dendrobium orchids. This research was carried out at CV Candi Orchid, 17 Bukit Unggul Raya Street, Semarang, over three months, from May to July 2023. The research design employed in this research is the two-tailed t-test research method, which includes a control group and an experimental group treated with 0.2% Eco Enzyme. There were two combinations, with each treatment comprising six replicates. The measured variables included the number of roots, root length, buds, and panicles. The outcomes indicated that the application of Eco Enzyme led to a significant increase in the number of panicles compared to the control group. However, no significant differences were observed in root length, the number of new roots, or the number of buds when Eco Enzyme was applied.